Responses of tree growth, leaf area and physiology to pavement in Ginkgo biloba and Platanus orientalis - Cui, Bowen; Wang, Xuming; Su, Yuebo; Gong, Cheng; Zhang, Danhong; Ouyang, Zhiyun; Wang, Xiaoke (Frontiers in Plant Science, 2022)
Trees growing on paved lands endured many environmental stresses in urban environment. However, it is less-known the morphological and physiological mechanisms underlying tree adaption to pavement in field. In this study, we investigated 40 sites where Ginkgo biloba and Platanus orientalis growing on adjacent pairs of paved and vegetated plots in parks and roadsides in Beijing, China. Relative to vegetated land, the mean increments in diameter at breast high and height in paved land were significantly decreased by 44.5% and 31.9% for G. biloba and 31.7% and 60.1% for P. orientalis, respectively. These decreases are related to both the decrease in assimilation products due to the reductions in leaf area, leaf total nitrogen content and chlorophyll content, and the increase in energy cost due to the synthesis of more soluble sugar and proline for mitigating stress. The increase in leaf soluble sugar content, proline content and δ13C indicated that trees could adapt to paved land through regulation of osmotic balance and enhancement of water-use efficiency. Piecewise structural equation models showed that trees growing on paved land are stressed by compounding impacts of leaf morphological and physiological changes. Therefore, it is critical to explore the complex response of plant morphological and physiological traits to pavement-induced stress for improving tree health in urban greening.